Manufacturing Process of Thinner Storage Tank with a Capacity of 226 Liters - Lukmanulhakim, Akmal; Santoso, Deri Teguh (TRANSMISI, 2025)
This research focuses on the manufacturing process of a thinner storage tank with a capacity of 226 liters. The objective is to identify the materials and process stages involved in producing the tank. The study employs a direct research and development methodology to explore this topic. For the tank’s body, SUS 403 stainless steel is selected for its excellent corrosion resistance, while ST45 steel is chosen for the frame due to its high load-bearing capacity. The manufacturing process includes material selection, cutting, rolling, welding, finishing, and quality control. In the welding phase, Gas Tungsten Arc Welding (GTAW) is utilized with ER308L filler, applying a current of 70 amperes for the tank body and 100 amperes for the tank head. For the frame, Shielded Metal Arc Welding (SMAW) is employed using RD260 2.6mm electrodes at a current of 90 amperes. The study aims to provide comprehensive insights into the selection and application of materials and processes for efficient tank.